Condições de trabalho e saúde de profissionais de Educação Física atuantes em academias da cidade de Pelotas - Hartwig, Tiago Wally (2012)
Introduction : The role of physical education professionals in gyms is a recognized profession recently , which along with other health services was identified in the late 1990s , as one of the sectors that develop during the twentieth century . However , there is a lack literary regarding information concerning working conditions and health of that professional working in gyms . Federal regulatory agencies such as Councils , Regional and Unions have the responsibility to verify the reality of these professional workers , such as wage issues , breaks , contractual , ergonomic conditions , among others . However , issues relating to compliance with those standards should be investigated in more depth . Additionally , there is evidence that this professional is more susceptible to health problems related to their health . Musculoskeletal problems , high exposure to noise , voice disorders , and mental strain may be associated with the work environment because of the characteristics of some types found in gyms . Objective: This study aims to determine the working conditions and health professionals working in these establishments . Methodology : This was a descriptive , observational , cross-sectional covering all physical education professionals working in academies of physical activity in the city of Pelotas . Data collection will be accomplished through pre-tested questionnaire and coded , containing questions related to the socioeconomic and demographic ( gender, age , skin color , marital status , and socioeconomic ) ; behavioral and nutritional factors (smoking , alcohol intake , level physical activity in different domains, and body mass index ), work-related ( work conditions through the profile and professional practice ) and health-related and musculoskeletal symptoms ( using the Nordic Questionnaire for musculoskeletal symptoms ) problems related to voice ( use of Quality of Life questionnaire and Voice ) , minor psychiatric disorders through the SRQ - 20 and evaluation of self-rated health